Correlation Between Climate Factors and Population Density with DHF Cases in Tanah Datar - Dayyan Shiddiq Budhidharma (Jurnal Kesehatan Medika Saintika, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease that is prone to occur in tropical areas. Tanah Datar Regency is one of the districts which is almost always among all the districts in West Sumatra Province with the highest DHF cases. This study aims to determine the correlation between climate factors and population density with DHF cases that occurred in Tanah Datar District in 2014-2022. This research uses cological studies. The dependent variabels are dengue cases per month and dengue case pe sub-district per year. The independents variabels are rainfall, air humidityy, air trmperature, wind speed, and population density. The data is secondary data that collected from Tanah Datar Health Department, West Sumatra BMKG, and District Tanah Datar BPS. The data used is data for 2014-2022 peiod. The results of this study indicate that in a trend, DHF cases incrase on the rainy season and decrease o the summer. Based on the results of the analysis conducted on DHF per month on climate factors per month showed that DHF was caused by the wind speed factor (p=0,022), while other factors did not affect DHF, rainfall (p=0,575), air humidity (p=0,456), and air temperature (p=0,328). The annual population densiti has an effect on the annual DHF incidence (p=0,001). The variables that related to DHF cases in Tanah Datar Regency from 2014 to 2022 are wind speed and population density